PERJALANAN DEMOKRASI DI INDONESIA - Purnamawati, Evi (Solusi, 2020)
Indonesia as one of the countries that adheres to a democratic system. The system of government is organized by the people, by the people, and for the people. Indonesia in the course of democracy underwent several periods, until now undergoing a period of reform. The diversity of the Indonesian people is a factor that greatly influences the birth of political parties and encourages the formation of a multiparty system in Indonesia. Democratic countries, of course, justify the existence of political parties as pillars of democracy or the exercise of popular sovereignty. Democracy is carried out through general elections in the context of occupying the leadership and power seats in which political parties are participants.